Lightweight concrete incorporating pumice based blended cement and aggregate: Mechanical and durability characteristics - Hossain, K.; Shaikh, Faiz; Lachemi, M. (Elsevier BV, 2011)
This paper presents the development of lightweight volcanic pumice concrete (VPC) using pumice based ASTM Type I blended cement (PVPC) and aggregates (both coarse and fine). The performance of VPC mixtures was evaluated by conducting comprehensive series of tests on fresh and hardened properties as well as durability. Fresh and mechanical properties of VPC mixtures such as slump, air content, compressive strength, tensile strength, density, and modulus of elasticity are described. The durability characteristics were investigated by drying shrinkage, water permeability, mercury intrusion porosimetry, differential scanning calorimetry and microhardness tests. The variables in the study include: % replacement (0%, 50%, 75% and 100% by volume) of normal weight coarse gravel aggregate by coarse lightweight volcanic pumice aggregate (VPA), replacement (100% by volume) of fine aggregate (sand) by fine VPA, constant (0.45)/variable (0.37-0.64) water-to-binder ratio by mass, variable (1.3-3.7) aggregate-to-binder ratio by mass and cement types (ASTM type I cement and PVPC). The investigation suggests the production of lightweight VPCs for structural applications having satisfactory strength and durability characteristics. The use of PVPC induces the beneficial effect of reducing the drying shrinkage and water permeability of VPC mixtures. The presence of coarse/fine/both VPA is also associated with lower permeability due to the development of high quality interfacial paste-aggregate transition zone and the progressive internal curing in VPCs. Development of non-expensive and environmentally friendly VPC with acceptable strength and durability characteristics (as illustrated in this study) can be extremely helpful for the sustainable construction and rehabilitation of volcanic disaster areas around the world. © 2010 Elsevier Ltd. All rights reserved.